2022
DOI: 10.1021/acs.jmedchem.1c02022
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Novel Peptide–Drug Conjugate Covalently Targeting SARS-CoV-2 Papain-like Protease

Abstract: Coronavirus disease 2019 (COVID-19) pandemic, a global health threat, was caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The SARS-CoV-2 papain-like cysteine protease (PLpro) was recognized as a promising drug target because of multiple functions in virus maturation and antiviral immune responses. Inhibitor GRL0617 occupied the interferon-stimulated gene 15 (ISG15) C-terminus-binding pocket and showed an effective antiviral inhibition. Here, we described a novel peptide–drug conjugate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…This approach to synthesize peptide-drug conjugates (PDCs) targeting SARS-CoV-2 PLpro appeared to improve on specificity toward the catalytic cysteine. Yet, these PDCs were still found to be nonselective for the other ten cysteines found in PLpro ( Liu et al, 2021a ). While peptide-based inhibitors remain an interesting avenue for development, the issues of their specificity for PLpro, and typically low oral bioavailability indicate that, as for Nirmatrelvir ( Owen et al, 2021 ), significant medicinal chemistry will be required to convert the peptidic features into more favourable drug-like properties.…”
Section: Overview Of the Plpro Inhibitor Binding Sitementioning
confidence: 96%
See 1 more Smart Citation
“…This approach to synthesize peptide-drug conjugates (PDCs) targeting SARS-CoV-2 PLpro appeared to improve on specificity toward the catalytic cysteine. Yet, these PDCs were still found to be nonselective for the other ten cysteines found in PLpro ( Liu et al, 2021a ). While peptide-based inhibitors remain an interesting avenue for development, the issues of their specificity for PLpro, and typically low oral bioavailability indicate that, as for Nirmatrelvir ( Owen et al, 2021 ), significant medicinal chemistry will be required to convert the peptidic features into more favourable drug-like properties.…”
Section: Overview Of the Plpro Inhibitor Binding Sitementioning
confidence: 96%
“…To improve on the efficacy of such inhibitors for PLpro, there have been recent attempts at combining the specificity of small molecules (such as GRL-0617 ) with the potency of covalent peptides or war heads ( Liu et al, 2021a ; Parks et al, 2021 ). In particular the latter manuscript, currently available as a preprint, discusses how GRL-0617 is derivatised to reach the catalytic Cys111, and a crystal structure shows that Leu162 indeed rotates again to open the congested channel typically observed in liganded PLpro structures.…”
Section: Overview Of the Plpro Inhibitor Binding Sitementioning
confidence: 99%
“…Liu et al reported the design of peptide–drug conjugates (PDCs) as covalent inhibitors of SARS-CoV-2 PL pro . 88 The PDCs consist of GRL0617 and cyclic sulfonium-containing peptides derived from PL pro substrate Leu-Arg-Gly-Gly ( Table 1 ). The sulfonium serves as a warhead and is designed to react with the C111.…”
Section: Sars-cov-2 Pl Pro Inhibitorsmentioning
confidence: 99%
“…Co-crystal structures highlighted the key interactions with the protease and verified the covalent inhibition mechanism. Li and coworkers used 19 as the starting point for their covalent inhibitor and appended a sulfonium-tethered peptide to generate a peptide drug conjugate [ 147 ]. Both strategies incorporated the glycine residues of the PLpro substrates to navigate the S1 and S2 sites.…”
Section: Papain-like Protease (Plpro)mentioning
confidence: 99%